2002
DOI: 10.1081/cnv-120001141
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and the Risk of Prostate Cancer

Abstract: Diabetics appear to have a lower risk of prostate cancer, though this effect may be limited to whites. An understanding of this association and its race specificity may help to explain the major difference in incidence rates for prostate cancer between blacks and whites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
3
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 25 publications
6
47
3
1
Order By: Relevance
“…7 A hospital-based casecontrol study in New York City also reported an association of similar magnitude. 10 We found no association between use of oral medications for diabetes and prostate cancer risk (HR 0.94, 95% CI 0.71-1.24), compared to subjects without diabetes. In the UK study, use of sulfonylureas was associated with a decreased risk (OR 0.60, CI 0.42-0.85), whereas no association was found for metformin use (OR 1.16, 0.63-2.14).…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…7 A hospital-based casecontrol study in New York City also reported an association of similar magnitude. 10 We found no association between use of oral medications for diabetes and prostate cancer risk (HR 0.94, 95% CI 0.71-1.24), compared to subjects without diabetes. In the UK study, use of sulfonylureas was associated with a decreased risk (OR 0.60, CI 0.42-0.85), whereas no association was found for metformin use (OR 1.16, 0.63-2.14).…”
Section: Discussioncontrasting
confidence: 60%
“…For example, although men with insulin-resistant type 2 diabetes may initially have increased levels of endogenous insulin, IGF-1 and leptin, as the disease progresses to insulin deficiency (the stage where insulin may be added as a therapy), levels of these factors decrease. 10,17,18 Insulin and IGF-1 may be involved in prostate cancer development through stimulating cell growth and proliferation. 11,15 Other factors, such as circulating leptin, have also been implicated in the development and progression of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later in 2006, another meta-analysis containing 19 studies (Wynder et al, 1971;Ragozzino et al, 1982;Mishina et al, 1985;Thompson et al, 1989;Smith et al, 1992;Steenland et al, 1995;Coughlin et al, 1996;Will et al, 1999;Rosenberg et al, 2002;Tavani et al, 2002;Weiderpass et al, 2002;Coker et al, 2004;Lightfoot et al, 2004;Zhu et al, 2004;Gonzalez-Perez et al, 2005;Rodriguez et al, 2005;Tavani et al, 2005) was published (Kasper et al, 2006). They both showed that diabetic patients have a statistically significant (9% in 2004 and 16% in 2006) decrease in the risk of developing PCa.…”
Section: Diabetes Mellitus Reduces Prostate Cancer Risk -No Function mentioning
confidence: 99%
“…Studies were excluded if they did not provide enough data to allow calculation of relative risks (RRs) with 95% confidence intervals (CI). Besides, publications were excluded if the exposure was metabolic syndrome (Laukkanen et al, 2004) or hyperglycemia (Grundmark et al, 2010), or controls were men with benign prostatic hyperplasia (Checkoway et al, 1987;Rosenberg et al, 2002), or the outcome was PCa mortality (Coughlin et al, 1996, Will et al, 1999 or recurrence (Chan et al, 2005). Additionally, publications were excluded if they were designed to clarify the association between DM and severity of PCa among patients having radical prostatectomy (Abdollah et al, 2011), or radiation therapy (Mitin et al, 2011), or having a prostate biopsy (Moreira et al, 2011) due to elevated PSA level.…”
Section: Selection Of Published Studiesmentioning
confidence: 99%